PRACTICE OF SAFETY CULTURE PRINCIPLES - Anjay Kumar Mishra, Khem Raj Joshi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Safety is not dependent only upon technology but also upon the culture. Exhibit Safety Leadership, Promote Safety in Design, Communicate Safety Information, Manage Safety Risk, Continuously Improve Safety Performance and Entrench Safety Practices are safety principle practiced in Construction Projects of developed countries assessed through a set of checklist in Lumbini Development Trust (LDT). The study shows the accidents rate with relation to workers’ experience for the enhancement of overall safety. The study shows the safety culture to be followed and enshrined by the various project stakeholders in all the phases of the project life cycle i.e. planning, designing, construction, and post-construction in construction industry of Nepal. It was found that majority of safety principles are led by the client in the three phases of construction i.e. planning, designing and post-construction. In the construction phase the principles are led by the contractors who are out of sight during other phases. The minor accidents decrease with the increase in the experience whereas major accidents increase with experience. The contractors, main implementer and responsible for safety should be equally presence in the other phases of construction. Projects should impart the safety training to the workers periodically.